Dinamika Peluang Dan Tantangan Medical Tourism Dalam Bingkai Hukum Indonesia - Gama Pandega (Perspektif Administrasi Publik dan hukum, 2024)
Medical tourism has become a significant global phenomenon in the last decade. This study aims to analyze the dynamics of medical tourism opportunities and challenges within the Indonesian legal framework. Medical tourism refers to the travel of individuals to other countries to obtain high-quality medical care at a more affordable cost. Indonesia, with its natural resource potential and growing medical facilities, is attracting increasing attention as a medical tourism destination. In this study, we explore the legal framework governing medical tourism in Indonesia and analyze its impact on the opportunities and challenges faced by the sector. We also consider factors such as standards of medical care, cross-sector regulations, consumer protection, and accountability of the medical profession. The research method involved an in-depth literature review of laws and regulations related to medical tourism in Indonesia as well as a comparative study with other countries that have successfully developed this sector. The analysis results show that Indonesia has great potential in developing medical tourism thanks to its natural wealth, cultural diversity and modern medical facilities. However, significant challenges also exist, including harmonization of regulations across sectors, improving standards of medical care, and legal protection for consumers and providers of medical services. Apart from that, the importance of maintaining medical ethics and information transparency in the promotion of medical tourism is also an important focus in the legal framework.